PELAKSANAAN TEKNIK SUPERVISI INDIVIDUAL GUNA MENINGKATKAN KINERJA GURU DALAM MENYUSUN SILABUS DAN RPP DI SD NEGERI 50 KOTA BANDA ACEH TAHUN PELAJARAN 2015/2016 - Nani Irawati (Jurnal Dedikasi Pendidikan, 2017)
Teachers are profession that requires special skills. The existence of the teachers for a nation is very important especially for the survival of the nation in the middle of the journey of the increasingly sophisticated technology era, all the changes as well as the shifts of. It brings consequences to the teacher to improve his or her role and competence. The Principal conducts the academic supervision to provide the assistance in the development and improvement of the teachers' performance in order to achieve national education objectives. Professional teachers have teaching experience, intellectual capacity, morals, faith, devotion, discipline, responsibility, broad educational insight, managerial skills, skilled, creative, professional openness in understanding potential, characteristics and developmental problems of the learners, able to develop the study plan and career of the learners and have the ability to research and develop the curriculum. The purpose of this study is to measure the improvement of the teachers’ performance in preparing syllabus and RPP after individual supervision technique. It has been done to the teachers who have compiled syllabus and RPP in previous year and the teachers who have not yet compiled syllabus and RPP. This research was conducted by classroom action research in 2 cycles. Each cycle consists of planning, implementation, observation and reflection. The researcher carried out the academic supervision. It includes traditional supervision and clinical supervision. The subjects of this study were all the classroom teachers and the subject teachers in SD Negeri 50 Kota Banda Aceh. The totatal numbers of the sample was 23 teachers. The results showed that there is an increasing in the teachers’ competence in preparing syllabus and RPP through individual supervision techniques in SD Negeri 50 Banda Aceh city. The teachers’ activities in the preparation of syllabus and RPP which are complete and systematic in the second cycle is better than at the first cycle.